2014
DOI: 10.1117/12.2040086
|View full text |Cite
|
Sign up to set email alerts
|

Internal quantum efficiency and tunable colour temperature in monolithic white InGaN/GaN LED

Abstract: Internal Quantum Efficiency (IQE) of two-colour monolithic white light emitting diode (LED) was measured by temperature dependant electro-luminescence (TDEL) and analysed with modified rate equation based on ABC model. External, internal and injection efficiencies of blue and green quantum wells were analysed separately. Monolithic white LED contained one green InGaN QW and two blue QWs being separated by GaN barrier. This paper reports also the tunable behaviour of correlated colour temperature (CCT) in pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A high IQE of ∼60% is derived at room temperature (300 K), which surpasses that of the film based conventional InGaN quantum wells in the similar visible wavelength range, shown in Figure 2d. 3,48,49 However, the PL emission efficiency by and large depends on excitation powers and nonradiative mechanisms at the low temperatures. For that reason, it is important to derive the IQEs over a broad range of excitation powers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A high IQE of ∼60% is derived at room temperature (300 K), which surpasses that of the film based conventional InGaN quantum wells in the similar visible wavelength range, shown in Figure 2d. 3,48,49 However, the PL emission efficiency by and large depends on excitation powers and nonradiative mechanisms at the low temperatures. For that reason, it is important to derive the IQEs over a broad range of excitation powers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, co-existence in the LED active region of quantum wells (QWs) emitting at different wavelengths complicates operation of the devices. It was observed that the ratio of the emission intensities from different QWs is very sensitive to the operating current [11,12] and continuouswave versus pulsed power supply [13], temperature [10,14,15], active region design, i.e. the number of QWs of each type and their relative positions in the LED structure [10,13,16,17], thickness and doping (type and level) of the barrier separating different QWs [12,15,[18][19][20][21], as well as to the growth conditions of the monolithic LED structures and strain [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A simpler fabrication approach of vertically stacked QWs emitting at two distinct wavelengths has been reported. Active region of such devices can consist of either: (i) longer wavelength emitting passive QWs pumped by active blue QW [16]; or (ii) all electrically pumped active QWs [8,11,17]. The first approach is similar to phosphor covered LEDs and the spectrum is controlled by number of passive QWs in active region.…”
Section: Introductionmentioning
confidence: 99%